2010
DOI: 10.2165/11538900-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Awareness, Compliance and Preferences among Hormonal Contraception Users

Abstract: These findings demonstrate that a range of factors influence a woman's choice of contraceptive. This highlights the importance of individualized counselling during contraceptive selection to ensure that the option recommended is tailored to the personal preferences of each woman to improve compliance, continuance and prevention of an unwanted pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 25 publications
4
71
0
7
Order By: Relevance
“…A qualidade da orientação oferecida às mulheres afeta de forma importante a aceitabilidade e continuação dos contraceptivos 15 . Tem sido descrito que dentro do primeiro ano de início do contraceptivo, 7 a 27% das mulheres interrompem o uso por razões que poderiam ter sido discutidas entre o médico e a paciente durante a consulta inicial de prescrição 16 . Revisões têm mostrado que em matéria de contracepção é necessário uma abordagem individual centrada nas necessidades individuais de cada mulher ou casal e que a relação interpessoal entre a paciente e seu médico é fundamental para obter êxito nesta matéria 16 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A qualidade da orientação oferecida às mulheres afeta de forma importante a aceitabilidade e continuação dos contraceptivos 15 . Tem sido descrito que dentro do primeiro ano de início do contraceptivo, 7 a 27% das mulheres interrompem o uso por razões que poderiam ter sido discutidas entre o médico e a paciente durante a consulta inicial de prescrição 16 . Revisões têm mostrado que em matéria de contracepção é necessário uma abordagem individual centrada nas necessidades individuais de cada mulher ou casal e que a relação interpessoal entre a paciente e seu médico é fundamental para obter êxito nesta matéria 16 .…”
Section: Resultsunclassified
“…Tem sido descrito que dentro do primeiro ano de início do contraceptivo, 7 a 27% das mulheres interrompem o uso por razões que poderiam ter sido discutidas entre o médico e a paciente durante a consulta inicial de prescrição 16 . Revisões têm mostrado que em matéria de contracepção é necessário uma abordagem individual centrada nas necessidades individuais de cada mulher ou casal e que a relação interpessoal entre a paciente e seu médico é fundamental para obter êxito nesta matéria 16 . Entretanto, no sentido oposto, uma revisão 17 avaliou a efetividade de diferentes técnicas para melhorar a aderência e as taxas de continuação de métodos hormonais de contracepção.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Most studies demonstrate that the total number of bleeding days with extended hormonal contraceptive cycles decreases over time. However, the high rate of unscheduled, albeit light, bleeding compromises this advantage and may be a cause for the often high dropout rate [4,6,11,16,18]. In menstrually signaled regimens, recommending a break varying between 3 and 7 days to stop longer bleeding episodes [11,16], dropout rates are high even though these regimens result in fewer bleeding days.…”
Section: Discussionmentioning
confidence: 99%
“…Other surveys have shown that 30-50% prefer amenorrhea, 40% prefer to bleed 2-4 times a year and 40% want regular monthly menses [2,3]. An 8-country survey found that 58% of women would accept irregular bleeding initially if they had fewer periods over time [4].…”
Section: Introductionmentioning
confidence: 99%